Circadian Time Organization of Professional Firemen: Desynchronization—Tau Differing from 24.0 Hours—Documented by Longitudinal Self-assessment of 16 Variables. (October 2013) - Reinberg, Alain; Riedel, Marc; Brousse, Eric; Floc'h, Nadine Le; Clarisse, René; Mauvieux, Benoît; Touitou, Yvan; Smolensky, Michael H.; Marlot, Michel; Berrez, Stéphane; Mechkouri, Mohamed
Abstract : We investigated the circadian synchronization/desynchronization (by field-study assessment of differences in period, τ, of 16 coexisting and well-documented rhythms) of 30 healthy firemen (FM) exposed to irregular, difficult, and stressful nocturnal work hours who demonstrated excellent clinical tolerance (allochronism). Three groups of FM were studied (A = 12 FM on 24-h duty at the fire station; B = 9 FM on 24-h duty at the emergency call center; C = 9 day-shift administrative FM) of mostly comparable average age, body mass index, career duration, chronotype—morningness/eveningness, and trait of field dependence/independence. The self-assessed 16 circadian rhythms were (i) physiological ones of sleep-wake (sleep log), activity-rest (actography), body temperature (internal transmitter pill probe), right- and left-hand grip strength (hand dynamometer), systolic and diastolic blood pressure (BP) plus heart rate (ambulatory BP monitoring device); (ii) psychological ones (visual analog self-rating scales) of sleepiness, fatigue, fitness for work, and capacity to cope with aggressive social behavior; and (iii) cognitive ones of eye-hand skill and letter cancellation, entailing performance speed (tasks completed/unit time) and accuracy (errors). Data (4–6 time points/24 h; 2 591 480 values in total) were gathered continuously throughout two 8-d spans, one in winter 2010–2011 and one in summer 2011. Each of the resulting 938 unequal-interval time series was analyzed by a special power spectrum analysis to objectively determine the prominent τ . The desynchronization ratio (DR: number of study variables with τ = 24.0 h/number of study variables × 100) served to ascertain the strength/weakness of each rhythm per individual, group, and season. The field study confirmed, independent of group and season, coexistence of rather strong and weak circadian oscillators. Interindividual differences in DR were detected between groups and seasons (χ 2, correlation tests, analysis of variance [ANOVA]). Moreover, in each group, both in winter and summer, a normal distribution was observed in the number of FM with rhythms with τ = 24.0 h, e.g., ranging from 5/16 (large desynchronization) to 16/16 (no desynchronization). Such a normal distribution with intraindividual stability over time (i.e., seasons) is consistent with the hypothesis of an inherited origin of a differential propensity to circadian desynchronization and which is supported by the distribution of τ s in winter and summer following the Dian-Circadian Genetic Model, i.e., with τ = 24.0 h, τ = 24.0 h + n (0.8 h), and τ = 24.0 h − n (0.8 h).